2005
DOI: 10.1128/mcb.25.8.2873-2884.2005
|View full text |Cite
|
Sign up to set email alerts
|

Class II Histone Deacetylases: from Sequence to Function, Regulation, and Clinical Implication

Abstract: Three fundamental issues in postgenomic biology are (i) how the amino acid sequence of a given human protein predicates its structure, function, and regulation; (ii) how a protein is compared to its paralogs, as well as to its orthologs and other homologous proteins in model organisms; and (iii) how related studies contribute to the understanding of human pathology and the development of efficacious diagnostic and therapeutic means. These fascinating issues have inspired us to conduct a comprehensive analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
307
0
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 372 publications
(315 citation statements)
references
References 170 publications
(226 reference statements)
5
307
0
3
Order By: Relevance
“…FK228, for example, shows some preference for class I HDACs, and tubacin specifically targets HDAC-6 (27,28). Therefore, the challenge is to develop a new generation of HDAC inhibitors with improved specificity for certain HDAC isoforms and an increased efficacy compared with the pan-inhibitors such as TSA and suberoylanilide hydroxamic acid (SAHA) (29).…”
Section: Discussionmentioning
confidence: 99%
“…FK228, for example, shows some preference for class I HDACs, and tubacin specifically targets HDAC-6 (27,28). Therefore, the challenge is to develop a new generation of HDAC inhibitors with improved specificity for certain HDAC isoforms and an increased efficacy compared with the pan-inhibitors such as TSA and suberoylanilide hydroxamic acid (SAHA) (29).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that HDAC5 is involved in transcription regulation, cell cycle progression, differentiation and apoptosis (Yang and Gregoire, 2005). Although HDACs have been implicated in tumorigenesis (Wade, 2001), the role of HDAC5 in the DNA damage response is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…Forty years later, it has become clear that lysine acetylation can target many cellular proteins in addition to histones. Similarly to phosphorylation, methylation or ubiquitination, lysine acetylation belongs to the panel of posttranslational modifications used by the cell to alter the specific properties of a given protein (Kouzarides, 2000;Yang, 2005;Yang and Gregoire, 2005). Lysine acetylation is a dynamic, reversible and tightly regulated protein modification.…”
Section: Introductionmentioning
confidence: 99%
“…This review is restricted to class IIa HDACs and will focus on the latest developments in the understanding of their regulation and biology. For more general information on HDACs, we respectfully refer the reader to previous excellent reviews from our colleagues (Bertos et al, 2001;Grozinger and Schreiber, 2002;de Ruijter et al, 2003;Legube and Trouche, 2003;Marks et al, 2003;Thiagalingam et al, 2003;Verdin et al, 2003;Yang and Seto, 2003;Blander and Guarente, 2004;Marmorstein, 2004;North and Verdin, 2004;Sengupta and Seto, 2004;Ekwall, 2005;Glozak et al, 2005;Nusinzon and Horvath, 2005;Yang and Gregoire, 2005).…”
Section: Introductionmentioning
confidence: 99%